Low Power Design And Layout Techniques For CMOS Mixed - Signal Circuits - Abdul Khalek, Mohd Faizal (2009)
This thesis investigates the proposed layout techniques that imitates the triple well process by doing it on the conventional process technology. This proposed layout is fabricated and the results show that the layout techniques managers to change the threshold voltage. However, there are certain issues that need to be dealt with the drain current effects of the layout.